BCS-BEC crossover in a system of microcavity polaritons - EASTHAM, PAUL (American Physical Society, 2005)
We investigate the thermodynamics and signatures of a polariton condensate over a range of densities, using a model of microcavity polaritons with internal structure. We determine a phase diagram for this system including fluctuation corrections to the mean-field theory. At low densities the condensation temperature Tc behaves like that for point bosons. At higher densities, when Tc approaches the Rabi splitting, Tc deviates from the form for point bosons, and instead approaches the result of a BCS-like mean-field theory. This crossover occurs at densities much less than the Mott density. We show that current experiments are in a density range where the phase boundary is described by the BCS-like mean-field boundary. We investigate the influence of inhomogeneous broadening and detuning of excitons on the phase diagram.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; polariton